PENGARUH INDIKATOR VARIABEL MONETER TERHADAP NILAI EKSPOR CRUDE PALM OIL (CPO) DAN KARET DI PROVINSI JAMBI - Abel, Zahra Aisyah; Nainggolan, Saidin (JALOW | Journal of Agribusiness and Local Wisdom, 2019)
This research aims to: (1) describe monetary variable indicators of the export value of CPO and rubber and find out the direct, and (2) indirect effects of monetary variable indicators on the export value of CPO and rubber in Jambi Province. The export value of CPO and rubber in Jambi Province fluctuated allegedly due to the influence of monetary variables directly or indirectly. The variables used in this research are exchange rates, inflation, interest rates, land area, number of farmers, production, prices, and GRDP of Jambi Province from 2000-2016. This research was processed using the Partial Least Square (PLS) method. From the results of the research obtained monetary variable indicators directly have an influence on the export value of CPO with p-value (0,000) <Î± (0,05) with a large effect coefficient of -0,808, and its indirect influence has a negative and significant influence on p-value ( 0,001) <Î± (0,05) with a large coefficient of influence -0.475. While the direct influence of monetary variable indicators on the value of rubber exports has a significant negative effect with p-value (0,001) <Î± (0,05) with a large coefficient of influence -0.769 and the indirect effect has a negative and significant influence on p-value (0.000 ) <Î± (0,005) with a large coefficient of influence -0,433. Keyword: Interest Rate, Inflation, Production, Price, GDRP